Local Rice Genetic Relationship Kuantan Singingi District Using Sequence-Related Amplified Polymorphism (SRAP) - Chairil Ezward; Irfan Suliansyah; Nalwida Rozen; Indra Dwipa (JERAMI : Indonesian Journal of Crop Science, 2021)
Rice (Oryza sativa L.) is an important food crop that is the staple food of more than half of the world's population because it contains nutrients that the body needs. Information on the genetic diversity of local rice scattered in the Kuantan Singingi Regency is still not available. Due to this fact, the genetic diversity of local rice can be identified by DNA analysis. A DNA-based molecular marker that can be applied as a plant genetic marker is SRAP. The SRAP (Sequence Related Amplified Polymorphism) marker system is one of the powerful molecular tools for the clarification of individual sex and estimating the genetic diversity of plant species. This study aims to determine the genetic relationship of rice plants in the Kuantan Singingi Regency through SRAP markers. Twenty-four (24) local genotype samples were used in this study. Observational data were processed using Ms. software. Excel and (NTSYS-pc) version 2.02. The results obtained 17 fragments in Primer M, which resulted in a similarity analysis between 71% to 100%. There are two (2) groups at 75% similarity, then there are five (5) groups at 81% similarity and there are four (4) groups that have 100% similarity. The results of this study are expected to be taken into consideration in developing rice breeding strategies in the future.